2017
DOI: 10.1097/iae.0000000000001488
|View full text |Cite
|
Sign up to set email alerts
|

Low Endophthalmitis Rates After Intravitreal Anti-Vascular Endothelial Growth Factor Injections in an Operation Room

Abstract: The standardized sterile technique in an operation room with laminar airflow showed very low rates of endophthalmitis at three European sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 20 publications
0
35
3
2
Order By: Relevance
“…Another retrospective analysis including 40,011 IVI performed in the OR reported an EO rate of 0.007% [72]. Freiberg et al [73] have recently reported the series of 134,701 IVI performed in an OR with laminar airflow, with a very low rate of EO of 0.0074% per injection.…”
Section: Peri- /Injection Management In Intravitreal Pharmacotherapymentioning
confidence: 99%
“…Another retrospective analysis including 40,011 IVI performed in the OR reported an EO rate of 0.007% [72]. Freiberg et al [73] have recently reported the series of 134,701 IVI performed in an OR with laminar airflow, with a very low rate of EO of 0.0074% per injection.…”
Section: Peri- /Injection Management In Intravitreal Pharmacotherapymentioning
confidence: 99%
“…Regarding the safety profile, the incidence of endophthalmitis did not significantly differ from those reported in the literature [37][38][39][40][41] . Based on the currently available scientific evidence, intravitreal injections performed at the operating room did not have lower rates of endophthalmitis than those performed in the office [21][22][23][37][38][39][40][41] .…”
Section: Discussionmentioning
confidence: 60%
“…The incidence of endophthalmitis after intravitreal injections of anti-VEGF or corticosteroids is low [37][38][39][40][41] . In a Retrospective, nationwide multicenter case series conducted in France, which evaluated 316,576 intravitreal injections, the overall incidence of endophthalmitis was 0.021% (2.1 in 10,000 injections) (95% CI, 0.016%À0.026%) 37 .…”
Section: Discussionmentioning
confidence: 99%
“…28 El medio hospitalario hace necesario un comentario sobre las inyecciones intravítreas. 29 Entre 2003 y 2016 se realizaron 134.701 inyecciones intravítreas en quirófano bajo flujo laminar con máximas condiciones de esterilidad en el Hospital Universitario Zealand de Dinamarca y en el Hospital Triemli de Zurich y la Clinica Universitaria de Bern (Suiza). La tasa de endoftalmitis fue del 0.0074 %, con solo 4 casos con cultivo positivo: tres por Staphylococcus Epidermidis y un caso por Proteus spp.…”
Section: Uveítis Infecciosasunclassified